2014
DOI: 10.1136/bcr-2013-010990
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular repair of direct carotid–cavernous fistula in Ehlers–Danlos type IV

Abstract: Ehlers-Danlos syndrome (EDS) type IV is a collagen vascular disease with an autosomal dominant inheritance caused by COL3A1 mutation. Patients with EDS type IV can present with organ rupture, spontaneous arterial dissections and ruptured aneurysms. Because of their propensity to form arterial dissections, aneurysms and rupture, they can develop carotid-cavernous fistula (CCF) after minor trauma or spontaneously. In EDS, it has been reported that even conventional catheter diagnostic angiography may result in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…This may be recognized by the affected individual because of sudden onset of a swishing sound in the temporal region of the head followed by injection of the veins of the eye, pain around the eye, and protrusion with slow loss of visual acuity. The only treatment is closure of the fistula, usually by an arterial catheter and coiling or occlusion of the carotid proximal to the fistula [Halbach et al, ; Linfante et al, ].…”
Section: Organ System Involvementmentioning
confidence: 99%
“…This may be recognized by the affected individual because of sudden onset of a swishing sound in the temporal region of the head followed by injection of the veins of the eye, pain around the eye, and protrusion with slow loss of visual acuity. The only treatment is closure of the fistula, usually by an arterial catheter and coiling or occlusion of the carotid proximal to the fistula [Halbach et al, ; Linfante et al, ].…”
Section: Organ System Involvementmentioning
confidence: 99%
“…Endovascular procedures carry a significant risk of arterial dissection and aneurysm formation and are not typically recommended 17 . However, there are case reports of successful endovascular procedures in affected patients 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Although a transvenous approach to cavernous sinus embolization may be less effective than transarterial embolization in the treatment of direct CCF, there is substantial risk associated with arterial access in patients with vEDS using this approach with reported mortality rates of up to 58% 3. Several authors have recommended a transvenous treatment approach for CCF in patients with vEDS; however, arterial puncture is often required in order to delineate the vascular anatomy 4. Other case reports have described direct distal arterial access within the neck requiring surgical cut-down 9.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize arterial vascular complications, several authors have suggested a transvenous route of cavernous sinus embolization in vEDS CCF 4 5. Despite this treatment strategy, arterial access is still commonly required in order to identify the precise anatomy of the cavernous sinus and to evaluate the fistulous venous drainage pattern 4…”
Section: Introductionmentioning
confidence: 99%